Carbon Based Electrochemical Capacitor in 1M H2SO4 Electrolyte - Mohd Abid, Mohd Asyadi Azam; RAJA ABDULLAH, RAJA IZAMSHAH; Mohamad, Noraiham; Azizan, Mohd Arif; Abdul Manaf, Nor Syafira (2013)
In this article, the EC electrode is mainly consists of AC (97%) and graphene (3%) was added to enhance the electrode’s conductivity. Graphene not only has unique physical and chemical properties but also provides a great opportunity to understand the fundamental chemical and physical processes involved in the complex systems [Candelaria, 2012]. The electrode fabrication starts with the slurry preparation. The material is weighing by using weight balance to produce a 20 g electrode. The materials used are AC, graphene, KS6, binder, and 60 g NMP. The viscosity of the slurry needed is ca. 10,000 MPa.s with 50% solid content. The mixing process is repeated if the viscosity does not achieve the general standard. 1M sulfuric acid (H2SO4) was used as electrolyte, and the CV and charge-discharge measurements were conducted in 0.0 – 1.0 V potential range by using Basic DC Voltammetry System.